THE FEATURES OF SYSTEM OF MANAGEMENT ACCOUNTING IN TRADE ORGANIZATIONS - T. Rogulenko (Вестник университета, 2016)
The article examines main approaches to the management accounting distribution, the methods of cost accounting in trade organizations are analyzed, the features of the system of budgeting in trade organizations are considered, the features of management accounting in the trade are analyzed.